Staging Work in the Corporatist State. Visual Propaganda in Fascist Italy and Peronist Argentina (1922-1955) - Schembs, Katharina (Jahrbuch für Geschichte Lateinamerikas, 2021)
Starting in 1922, Benito Mussolini (1922-1943) reformed Italian labour relations by adopting corporatism. As such, he served as a model for many other heads of state in search of ways out of economic crisis. When the corporatist model spread throughout Latin America in the 1930s and 1940s, the Argentine president Juan Domingo Perón (1946-1955) drew significantly on the Italian precedent. Adhering to an aestheticised concept of politics and making use of modern mass media, both regimes advertised corporatism in their respective visual propaganda, in which the worker came to play a prominent role. The article analyses parallels and differences in the formation of political identities in fascist and Peronist visual media that under both corporatist regimes centred around work. Comparing different role models as they were designed for different members of society, I argue that – apart from gender roles where Peronism resorted to similarly traditional images – Peronist propaganda messages were more future-oriented and inclusive. Racist exclusions of parts of the population from the central worker identity that increasingly characterised fascist propaganda over the course of the 1930s were not adopted in Argentina after 1945. Instead, in state visual media the category of work in its inclusionary dimension served as a promise of belonging to the Peronist community.
Keywords: Corporatism; Identity Formation; Italian Fascism; Peronism; Visual Media; Propaganda